Influence of the Type of Epoxy Resin and Concentration of Glycidylisobutyl-POSS in the Properties of Nanocomposites. Issue 8 (October 2017) - Longhi, Marielen; Zini, Lucas Pandolphi; Kunst, Sandra Raquel; Zattera, Ademir José
Epoxy resin is one of the most used resins for obtaining composites and coatings. Its properties have been modified using many materials, mainly based on nanotechnology, such as clays and polyhedral oligomeric silsesquioxanes (POSS). POSS may increase thermal and mechanical resistance and hydrophobicity of the epoxy resin. This study aims at characterizing epoxy nanocomposites, using two distinct resins (DGEBA and DGEBF) and an addition of glycidylisobutyl-POSS in contents of 2.5% and 5% (w/w), through X-ray diffraction (XRD), Fourier transform infrared spectroscopy (FTIR), thermogravimetric analysis (TGA) and dynamic mechanical analysis (DMA). Samples showed an amorphous halo due to the epoxy resin and a characteristic peak of POSS. TGA results showed a greater residual mass in DGEBF systems due to its wider formation of crosslinks. FTIR spectra demonstrated a higher amplitude of the hydroxyl band in DGEBF 5% system, which may affect its hydrophilic behavior because of the molecular mobility and resin weight reduction. DMA results showed that DGEBA systems are more flexible than DGEBF.